Application of microscale culture technologies for studying lymphatic vessel biology. (2nd May 2019) - Chang, Chia‐Wen; Seibel, Alex J.; Song, Jonathan W.
Abstract: Immense progress in microscale engineering technologies has significantly expanded the capabilities of in vitro cell culture systems for reconstituting physiological microenvironments that are mediated by biomolecular gradients, fluid transport, and mechanical forces. Here, we examine the innovative approaches based on microfabricated vessels for studying lymphatic biology. To help understand the necessary design requirements for microfluidic models, we first summarize lymphatic vessel structure and function. Next, we provide an overview of the molecular and biomechanical mediators of lymphatic vessel function. Then we discuss the past achievements and new opportunities for microfluidic culture models to a broad range of applications pertaining to lymphatic vessel physiology. We emphasize the unique attributes of microfluidic systems that enable the recapitulation of multiple physicochemical cues in vitro for studying lymphatic pathophysiology. Current challenges and future outlooks of microscale technology for studying lymphatics are also discussed. Collectively, we make the assertion that further progress in the development of microscale models will continue to enrich our mechanistic understanding of lymphatic biology and physiology to help realize the promise of the lymphatic vasculature as a therapeutic target for a broad spectrum of diseases.